PERNIKAHAN MULTIKULTURAL (PERNIKAHAN ANTAR AGAMA PERSPEKTIF HUKUM ISLAM) - Ali Mohtarom (Universitas Yudharta Pasuruan, 2017)
The social dynamics that occur in society and the development of communication system leads to the phenomenon of different cultural marriages among the people of Indonesia. Marriage is something sacred and certainly awaited everyone. Whatever the case, relationships in marriage must be maintained, including in mixed marriages that are vulnerable to problems. Intercultural marriages or so-called mixed marriages are in fact marriages between men and women of different nationalities or nationalities, different beliefs (religions), and different origins.